An analysis on automated waste collection system in Klang Valley / Faizal Abu Bakar - Abu Bakar, Faizal (2012)
Waste is the thing that is produced by human for every day and the capacity of waste has increase from day to day. So, the waste management is very important for the human in this world and it must have a systematic and strategic system to manage the waste. In this world especially in Malaysia, do not have enough landfill to support all the waste or garbage that is produce by human. Therefore, the parties involve must has a good strategies to manage the waste or garbage. From the situation, many systems that are apply in the building to help the management of the waste. For example the Automated Waste Collection System (AWCS) where this system is to help the people in the building to throw the garbage and the garbage will be bring to the garbage store at the external of the building. Much of machinery that is involved in this system such as compressor, centrifugal fan, sensor, discharge valve, and others. The objectives of this research are to study, to identify the management and to analyze the Automated Waste Collection System (AWCS). The building that is choosing for the case study is Customs Complex of Kelana Jaya, South Integrated Transport Terminal (TBS) and Maju Holdings Tower. The three case study building has use the different type of the system on the management of the waste. Literature review is the first stage to carry out for the research and followed by observation, interview and distribute the questionnaire. The questionnaire that has been prepared will distributed to the user or visitor to see their perception and satisfaction on the using the Automated Waste Collection System (AWCS).